Elaboración de un modelo de reinversión de capital adecuado para obtener la eficiencia en el sistema articulado de la Cooperativa de Ahorro y Crédito 23 de Mayo Ltda. - García Ortíz, Guillermo Mauricio (2006)
In this paper the work of a Manager and guidelines to consider when managing a Savings and Credit Cooperative is exposed, highlighting the knowledge that this professional must possess to lead the way to the development and growth of these organizations.